Water sorption-based thermochemical storage materials: A review from material candidates to manufacturing routes - Palacios, Anabel; Navarro, Maria Elena; Barreneche, Camila; Ding, Yulong (Frontiers in Thermal Engineering, 2022)
A comprehensive and updated review is provided in this paper with a focus on water-sorption-based thermochemical storage (TCS) materials, covering materials and their characterization and manufacturing. A comprehensive review is then presented on the 22 most relevant salt hydrates (bromides, sulfates, carbonates, chlorides, nitrates, hydroxides and sulphides) candidates. This is followed by a discussion on TCS materials manufacturing, covering both conventional (shaping, pelletizing, etc) and more advanced routes (e.g. extrusion, 3D printing, encapsulation, etc). Finally, concluding remarks are presented, including limitations and future potentials for the TCS research